Electronic lexicography - Granger, Sylviane (Oxford University Press, 2012)
This book brings together leading professional and academic lexicographers to report on current developments in the deployment of electronic means in the planning, writing, and dissemination of dictionaries. Every major aspect of electronic lexicography is covered by the book including dictionary types (general and specialized dictionaries, monolingual and multilingual dictionaries, collocation dictionaries, sign dictionaries, collaborative dictionaries) in a range of formats (CD-ROM, web-based, handheld), dictionary-writing systems, integration of corpora, The book also addresses the implications of electronic dictionary-making for lexicographic theory and illustrates how the new developments are integrated into innovative dictionary projects like Wiktionary. The perspective of the user is considered throughout the book, including how electronic dictionaries take account of user needs and whether and how users take advantages of the new features afforded by the electronic medium. This state-of-the-art account of developments in one of the most vibrant areas of reference publishing and language research will appeal to everyone concerned with current lexicography